Network-based macro fluctuations: What about an open economy? - Mihnea Constantinescu; Kristina Barauskaite (Baltic Journal of Economics, 2018)
Do input-output linkages of intermediate products affect the spread of sectoral shocks at the aggregate level in Lithuania, a small and open economy? What role does openness play in the empirical exercise? We answer these questions by: (i) constructing the Lithuanian input-output transactions tables with domestic-only and domestic and imported sector-by-sector direct requirements, and (ii) applying Acemoglu, Carvalho, Ozdaglar, and Tahbaz-Salehis [(2012). The network origins of aggregate fluctuations. Econometrica, 80(5), 1977-2016] network-based methodology and Gabaix and Ibragimov's [(2011). Rank-1/2: A simple way to improve the ols estimation of tail exponents. Journal of Business & Economic Statistics, 29(1), 24-39] modified log rank-log size regression. Our results indicate that the structure of input-output linkages cause aggregate economic volatility to decay at a rate lower than the established theoretical prediction. Indirect linkages play an equally important role for both domestic-only and aggregated domestic and import transactions.
Keywords: C13; C46; C67; E00; 330; Input-output network; aggregate volatility; small-open economy; complexity economics